Peningkatan Partisispasi Peserta Didik dalam Belajar IPA Melalui Model Problem Based Learning - Zulfi Idayanti; Tsaqifa Taqiyya Ulfah; Izzatin Kamala (Jurnal Penelitian Pendidikan IPA, 2022)
Science learning is a very important lesson for all people, especially elementary school students. Based on the 2013 curriculum, learning refers to students. Student activity in learning is very important, but based on the facts, student participation tends to be low. Observing this situation, the researcher adopted the Problem Based Learning (PBL) learning model. The research method used is Classroom Action Research (CAR) using the Kemmis and Taggart models with the research subject being the fourth grade students of SD Negeri Demangan totaling 25 students and 1 class teacher. This research was carried out in 2 cycles consisting of planning, implementation, observation and reflection. The research instrument consisted of observation sheets, learning tools, Student Worksheets (SW), post test grids and post test question sheets. The data collection technique used by the researcher is in the form of a test at the end of each cycle and non-test consisting of observation, interviews and documentation. Technical data analysis is in the form of qualitative data analysis about how the activities of students and teachers and quantitative analysis is about the learning outcomes achieved by students at the end of each cycle. The implementation of research actions is carried out in 5 stages, namely orientation of students to problems, organizing students to learn, guiding individual/group experiences, developing and evaluating problem solving processes. The results showed that after the implementation of the Problem Based Learning learning model, student participation during learning increased. This can be proven by the participation of students in cycle 1 meeting 1 showing an average of 75% in the high category. At the second meeting, it decreased 2% to 73% with the same category, namely high. Then it increased again in cycle 2 meeting 1 with an average of 84% in the very high category and increased again to 89%. This shows an escalation in the participation of Class IV students at SD Negeri Demangan in science learning. At the second meeting, it decreased 2% to 73% with the same category, namely high. Then it increased again in cycle 2 meeting 1 with an average of 84% in the very high category and increased again to 89%. This shows an escalation in the participation of Class IV students at SD Negeri Demangan in science learning. At the second meeting, it decreased 2% to 73% with the same category, namely high. Then it increased again in cycle 2 meeting 1 with an average of 84% in the very high category and increased again to 89%. This shows an escalation in the participation of Class IV students at SD Negeri Demangan in science learning